Boosting activity of Fe-N4 sites in single-Fe-atom catalysts via S in the second coordination sphere for direct methanol fuel cells - Zhang, Jincheng (2023)
Developing low-cost and highly efficient oxygen reduction reaction (ORR) catalysts with excellent methanol tolerance is crucial for the commercialization of direct methanol fuel cells (DMFCs). In this work, we construct single Fe atoms anchored on N,S-codoped graphene (Fe1/NSG), where the S atom in the second coordination sphere of the Fe catalytic center regulates the electronic structure of the Fe center and stabilizes the ∗OOH intermediate in the ORR. Thanks to the optimal adsorption of O2 intermediates and the isolated Fe active sites, as probed by in situ infrared spectroscopy and density functional theory, Fe1/NSG exhibits high ORR activity with a half-wave potential of 0.90 V vs. reversible hydrogen electrode (RHE) and a super anti-methanol capability. The DMFC with the Fe1/NSG cathode is able to deliver a peak power density as high as 198 mW cm−2, outperforming the reported DMFCs assembled using non-precious-metal-based cathode catalysts.